Image Contrast Improvement in Interference-Dark-Field Digital Holographic Microscopy - Chi-Ching Chang (MDPI AG, 2021)
Conventional dark-field digital holographic microscopy (DHM) techniques require the use of specialized optics, and, thus, obtaining dark-field images with high contrast has a high cost. Herein, we propose a DHM system that uses an interference-dark-field technique for improving image contrast. Unlike conventional dark-field DHM, the proposed technique does not require expensive and specialized optical elements, or a complicated optical setup, to obtain dark-field images. The proposed technique employs a pure optical basis method to suppress scattering noise—namely, interference-dark-field—and mainly adopts an arbitrary micro-phase shifting method to achieve destructive interference for obtaining holograms. Under the framework of the proposed technique and through the observation of the USAF 1951 resolution target, the reconstructed image can retain the high contrast of the interference-dark-field DHM. The image contrast is enhanced by at least 43% compared to that which is obtained by conventional dark-field DHM. The resolution of the system can be as high as 0.87 μm. The proposed technique can switch between bright-field and dark-field DHM and prevents damage to the sample, which results from high-intensity illumination in conventional techniques.